The role of the dentist in the treatment of patients with tinnitus - Wójcicki, Marcin; Szkutnik, Jacek; Różyło-Kalinowska, Ingrid (Journal of Stomatology, 2019)
Tinnitus is a sensation of noise (such as ringing, roaring, buzzing, or whistling) without any external physical source of that sound. It affects about 15% of the adult population, of whom 2.5% report severely disturbing tinnitus. It is believed that temporomandibular disorders (TMD) are correlated with tinnitus. According to different studies, from 7% to 60% of patients with TMD also report tinnitus. The aim of this study was to point out the role of the dentist in managing patients with tinnitus. Untreated tinnitus can lead to serious debilitation and provoke suicidal tendencies. It is crucial to notice acute pulsating tinnitus, tinnitus with sudden, acute hearing loss, and acute post-traumatic tinnitus because these conditions are potentially life-threatening and require immediate referral to otolaryngologist. Worth noting is that similar psychological factors involved in the development of TMD (stress, depression, somatisation) also affect the generation of tinnitus. It is important to properly diagnose tinnitus and address it. Because of frequent coexistence of tinnitus and TMD, patients reporting to the dentist with TMD should be also asked about tinnitus. Different possible aetiologies and many factors involved in the onset and progression of tinnitus can impede the diagnosing process, which leads to the requirement of a multidisciplinary approach as well as discipline and cooperation on the part of the patient and the doctor.